Preparation and identification of oxidatin derivaties for Salts and acids of bile for medical uses (Baghdad Science Journal, 2004)
The purified prepared compounds were identified through different methods of identification i.e, I.R, UV-vi^ble-spectroscopy in addition to (coloured tests) Calculation of the sum of OH groups. TLC techniques were also used to test the purity and the speed ofthe rate of flow (RF).